Sintesis Nanofiber PVP dengan Ekstrak Basella rubra Linn. Menggunakan Metode Elektrospinning - Wulandari Kusuma Dewi; Defi Nur Indahsari; Okky Putri Prastuti; Eka Lutfi Septiani (Politeknik Negeri Malang, 2021)
An alternative wound dressing based on nanofiber mats have been developed recently. The antioxidant and antibacterial activity play an important role in wound healing process. This study aims to combine the properties of Bassela rubra Linn. (EBRL) extract into polivynil pyrrolidone (PVP) nanofibers using the electrospinning method. The first step is to weigh 8 grams of basella rubra linn and wrap it in filter paper. Then extracted using 99% ethanol as a solvent at a temperature of ± 78 oC. The next step is to make nanofibers using the electrospinning method by weighing 8% wt of PVP (Polyvinyl pyrrolidone). Basella rubra linn extract as much as 2% wt, 5% wt and 8% wt in the solution into a syringe. Then assistance with the flow rate of 1 mL / hour, the distance between the spineret and the collector is 10 cm, coating the collector with aluminum foil, and providing 12kV voltage assistance. In the application of nanofibers with EBRL, a certain fiber size is required, so in this study, we observed the impact of EBRL on its diameter and distribution. This method begins by injecting PVP and EBRL solutions of various compositions into the collector in a set of electrospinning devices. The morphology of the nanoparticles was analyzed using the Scanning Electron Microscopy (SEM) method. Differences in the composition of EBRL provide different diameter and diameter distribution. This can be constructed by the Taylor Cone form of the solution that is injected.